Neuroendocrine Responses to Transvascular Autonomic Modulation: A Modified Balloon Angioplasty in Multiple Sclerosis Patients - Arata, M.; Sternberg, Z. (Hormone and Metabolic Research, 2016)
Balloon angioplasty (BA) is a treatment modality to correct vascular lesions in multiple sclerosis (MS) patients, who present with chronic cerebrospinal venous insufficiency (CCSVI). We hypothesized that BA clinical benefits stems in part from improvement in cardiovascular autonomic nervous system (ANS) function. We adopted the Transvascular Autonomic Modulation (TVAM), as a modified BA technique, with the objective of further enhancing ANS functional activities. TVAM involved dilation of multiple vascular beds, including IJVs, azygos and renal veins, and application of manual compression. Since the ANS regulates the function of the hypothalamus pituitary (HPA) axis, we examined TVAM effects on HPA axis in MS patients, and determined the relationship between ANS function and HPA activity. The adrenocorticotropic hormone (ACTH) and cortisol serum levels, systolic and diastolic blood pressure (BP), and heart rate variability (HRV) parameters were measured before and 24 h after TVAM procedure in 72 MS patients. Baseline ACTH and cortisol serum levels were lower than normal ranges in 18% and 25% MS patients respectively. The intervention resulted in significant reductions in both ACTH and cortisol (p<0.001), with a more marked ACTH reduction in males compared to females (p<0.001). Post-TVAM BP increased in patients who presented with baseline BP within lower limits of normal ranges, but decreased in patients with baseline BP above the normal ranges. In a univariate analysis, the changes (Δ) in ACTH serum levels correlated weakly, although significantly, with Δ in diastolic BP (r=−0.265, p=0.03), and Δ in cortisol serum levels correlated weakly, but significantly, with Δ in systolic BP (r=−0.283, p=0.01). The observed ACTH and cortisol reductions are counter to the stress-mediated increases in serum levels of these hormones, which are expected following an invasive procedure. The clinical implications of this unexpected response warrant further investigations.
Keywords: autonomic function; balloon angioplasty; blood pressure; CCSVI; HPA axis; heart rate variability